Audit of Compliance with the WHO Surgical Safety Checklist in the Orthopedic Operating Theatre at Benazir Bhutto Hospital - Zafar, Muhammad Hassan; Waleed, Usman; Bukhari, Maira; Farooq Khan, Muhammad Omer; Awan, Bilal Shoukat; Saeed, Muhammad Rawal (Biological and Clinical Sciences Research Journal, 2025)
The World Health Organization (WHO) Surgical Safety Checklist (SSC) has been shown to reduce peri-operative harm, but its real-world effectiveness is contingent on consistent, high-quality application. Global evidence indicates considerable variability in adherence, with the sign-out phase frequently showing the poorest compliance. Objective: To evaluate baseline SSC compliance in an orthopedic operating theatre, implement a targeted, low-cost intervention, and reassess compliance in a closed-loop audit. Methods: A closed-loop clinical audit was conducted at the Orthopedic Operating Theatre, Benazir Bhutto Hospital, Rawalpindi, Pakistan. In Cycle 1 (December 2024), 30 consecutive orthopedic surgeries were directly observed using a standardized SSC compliance tool. After the baseline assessment, a multifaceted intervention—comprising a department-wide educational session for surgeons, anesthetists, nurses, and residents; placement of laminated SSC posters at each operating table; and senior-staff verbal reinforcement and coaching—was implemented in February 2025. In Cycle 2 (June 2025), 30 new surgeries were observed by the same team using identical methods. Compliance for each SSC phase (sign-in, time-out, sign-out) was categorized as full (all items completed and verbalized), partial, or non-compliant. Descriptive statistics were applied to compare pre- and post-intervention proportions. Results: At baseline, full compliance was 40% for sign-in, 30% for time-out, and 20% for sign-out; overall, 30% of surgeries were fully compliant, 36% partially compliant, and 34% non-compliant. Following the intervention, full compliance increased to 80% (sign-in), 70% (time-out), and 65% (sign-out); overall, 72% of surgeries were fully compliant, 21% partially compliant, and 7% non-compliant. The most notable improvement occurred in the sign-out phase, which rose from 20% to 65% full compliance. Conclusion: A straightforward, low-cost intervention—combining education, visual reminders, and leadership engagement—more than doubled overall SSC full compliance in a high-volume orthopedic theatre within six months. Embedding such strategies into routine practice, alongside continuous monitoring and reinforcement, is likely essential to sustain improvements.